Assignment and routing model for the planning of fruit and vegetable supply operations in the southern part of Bogota - Herrera Ochoa, Oscar Javier; Orjuela Castro, Javier Arturo (Ingeniería Solidaria, 2022)
Introduction: This article is the product of the research Design of the logistics operation of food distribution in different locations south of Bogotá based on a multistage model, carried out during 2014 in the city of Bogotá.Problem: Bogota City has a big problem in its food supply framed by the inefficiency in the capillary distribution, raising costs to households, which generates difficulties in accessing food mainly to strata 1 and 2.Objective: Define a strategy for the planning of the efficient supply operation of fruits and vegetables to the south of the city.Method: An analysis of the behavior of the system proposed by the the Master Plan for Supply and Food Security of Bogotá was carried out, using a correlational descriptive method for the analysis of the variables, from the characterization of food in 4 locations, and other secondary sources.Results: In the first phase of this model, it was determined the allocations of the load to be distributed from three (3) logistic platforms towards 4 localities based on mixed integer mathematical programming. In the second phase, a basic VRP model was developed that allowed to determine the routing of vehicles with the remaining fruit and vegetables loads to be delivered.Conclusions: The work is relevant as a contribution to the optimal management of food supply through the use of mathematical models, given that it covers fixed costs both for deposits and for the use of vehicles, with a two-phase model. This can contribute to food security through greater access to food with reduced prices and timely availability in the target areas of study.Originality: Staged models that complement each other to define the complete food supply operation.Limitations: The models must be used with a minimum of knowledge on the subject.